Digital citizenship and discrimination in master of law programs in Cusco- Peru 2023 - Romani Miranda, Úrsula Isabel (2024)
The present research work is inherent to how to confront discrimination in Peru, particularly in the Cusco Region, from a regulatory proposal of the postgraduate units of two universities in Cusco. Given that even in the 21st century, manifestations of various forms of discrimination continue to be observed, such as: ethnic, linguistic, origin, social, economic, ideological, gender, among others. In this sense, the main objective of the work is to establish comparative criteria of mechanisms and use of digital citizenship to confront discrimination in the Law Master’s Program of the Andina University of Cusco and the San Antonio de Abad National University of Cusco. In Semester 2023-I, therefore, the methodology applied is a qualitative research approach with phenomenological design, assuming a population and census sample with intentionality. Finally, the comparison criteria were obtained: the subcategories of digital citizenship.